1989
DOI: 10.1071/ch9890895
|View full text |Cite
|
Sign up to set email alerts
|

Lewis-Base Adducts of Group 11 Metal(I) Compounds. LI. Synthesis and Structural Characterization of Mononuclear Chloro-, Bromo- and Iodo-pyridinebis(triphenylphosphine)copper(I) Complexes

Abstract: Complexes [ XCu ( py )(PPh3)2], X = Cl, Br, I, py = pyridine, have been synthesized and characterized by single-crystal X-ray structure determination. Chloride and iodide derivatives have similar cells [ isomorphous (?) but not isostructural ], triclinic, pi, a = 19.5 A, b = 10.5, c = 9.6 � , α ≈ 66, β ≈ 86, γ ≈ 83�, Z = 2; the bromide is monoclinic, Cc, a 13.568(9), b 15.760(12), c 16.545(8) � , β 95.65(5)�, Z = 4. Cl, Br, I structures were refined to residuals of 0.042, 0.055, 0.039 for 4288, 2241, 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
4
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 0 publications
3
4
0
Order By: Relevance
“…Crystal structures of 1-X prepared herein were identical to those reported by Engelhardt et al [21].…”
Section: Crystal Structuressupporting
confidence: 71%
“…Crystal structures of 1-X prepared herein were identical to those reported by Engelhardt et al [21].…”
Section: Crystal Structuressupporting
confidence: 71%
“…[4,5] In ref. [1] the authors commented that "no evidence has been ] dimers. TDDFT/CPCM calculations were used to clarify the type of transitions involved in the UV/Vis absorption spectra, and the corresponding experimental photoemission data were acquired.…”
Section: Introductionmentioning
confidence: 95%
“…In extending existing studies [1][2][3] to encompass the pseudohalogen X = SCN, it was found that crystallization of [Cu(SCN)(PPh 3 )] from pyridine yielded a complex shown to be a 1:1:2 CuSCN/PPh 3 /py adduct (2), the first of that stoichiometry so defined. It was found to crystallize in a chiral space group and to be strongly luminescent, which prompted study of its photophysical properties, augmented by the synthesis and study of a number of N ∧ Nbidentate ligand counterparts: a new polymorph of [Cu(NCS)(phen)(PPh 3 )] (4) and [Cu(NCS)(bpy)L] (L = PPh 3 , PPh 2 py) (5, 6), all mononuclear.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…As a result, the complex as such is conformationally chiral. A search in the Cambridge Structural Database (CSD; Version 5.27; Allen, 2002) revealed only four similar structures: [CuX(PPh 3 ) 2 (pyridine)], with X = Cl, Br or I (Engelhardt et al, 1989), and [CuI(PPh 3 ) 2 (imidazole)] (CSD refcode: DAFLAY; Wu et al, 2004). These four structures display the same arrangement of ligands around the Cu atom as does (I), except for [CuBr(PPh 3 ) 2 -(pyridine)], where the two triphenylphosphine ligands are mirror images of each other, making the complex achiral.…”
Section: Commentmentioning
confidence: 99%